Clinical and Economic Evaluation of Transdermal Oxybutynin in the Treatment of Overactive Bladder in Spain - Carlos Crespo; Pedro Blasco; Marcelo Guigini; Jordi Galván (Journal of Health Economics and Outcomes Research)
**Background:** This study evaluated the clinical outcomes and economic results of transdermal oxybutynin compared to fesoterodine, tolterodine, solifenacin, oxybutynin, trospium chloride, and mirabegron for overactive bladder syndrome in Spain.